2020
DOI: 10.3390/nano10071299
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Thermal Stability, and Catalytic Activity of Compounds Formed in CaO-SiO2-Cr(NO3)3-H2O System

Abstract: In this work, the thermal stability, microstructure, and catalytic activity in oxidation reactions of calcium silicate hydrates formed in the CaO-SiO2-Cr(NO3)3-H2O system under hydrothermal conditions were examined in detail. Dry primary mixture with a molar ratio of CaO/SiO2 = 1.5 was mixed with Cr(NO3)3 solution (c = 10 g Cr3+/dm3) to reach a solution/solid ratio of the suspension of 10.0:1. Hydrothermal synthesis was carried out in unstirred suspensions at 175 °C for 16 h. It was determined that, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…These minor changes indicated the higher thermal stability of silica based nano-formulations. In a recently conducted research 88 , researchers reported the higher thermal stability of calcium silicate hydrate (CaO-SiO 2 -Cr(NO 3 ) 3 -H 2 O) upto > 550 °C. The calcium silicate hydrate are thermally stable up-till 500 °C, and starts to change the physical properties and chemical composition at the temperature greater than 550 °C.…”
Section: Resultsmentioning
confidence: 99%
“…These minor changes indicated the higher thermal stability of silica based nano-formulations. In a recently conducted research 88 , researchers reported the higher thermal stability of calcium silicate hydrate (CaO-SiO 2 -Cr(NO 3 ) 3 -H 2 O) upto > 550 °C. The calcium silicate hydrate are thermally stable up-till 500 °C, and starts to change the physical properties and chemical composition at the temperature greater than 550 °C.…”
Section: Resultsmentioning
confidence: 99%
“…These minor changes indicated the higher thermal stability of silica based nanoformulations. In a recently conducted research, 73 reported the higher thermal stability of calcium silicate hydrate (CaO-SiO 2 -Cr(NO 3 ) 3 -H 2 O) upto 550°C. The calcium silicate hydrate are thermally stable up-till 500°C, and starts to change the physical properties and chemical composition at the temperature greater than 550°C.…”
Section: Thermal Degradationmentioning
confidence: 99%